2019
DOI: 10.1073/pnas.1914661116
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent structural plasticity at pre- and postsynaptic sites of layer 2/3 cells in developing visual cortex

Abstract: The developing brain can respond quickly to altered sensory experience by circuit reorganization. During a critical period in early life, neurons in the primary visual cortex rapidly lose responsiveness to an occluded eye and come to respond better to the open eye. While physiological and some of the molecular mechanisms of this process have been characterized, its structural basis, except for the well-known changes in the thalamocortical projection, remains obscure. To elucidate the relationship between synap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 62 publications
8
30
0
Order By: Relevance
“…While baseline spine dynamics at the apical dendrites of L2/3 pyramidal neurons was similar between adult PSD-95 WT and KO mice, a brief MD (4 d) led to a more than twofold increase (∼126%) in spine elimination in adult PSD-95 KO but not WT mice, and to a ∼70% increase in spine elimination in PSD-95 knockdown neurons in a WT environment. These results in PSD-95-deficient adult V1 neurons are very similar to the ∼100% increase in spine elimination previously observed for L2/3 apical dendrites of juvenile (P28) WT mice after a 3-d MD (19). For L5 apical dendrites of juvenile WT mice, pronounced spine elimination (>70% increase) after a 3-d MD has also been reported (20), but so far not for adult mice beyond the critical period.…”
Section: Discussionsupporting
confidence: 87%
“…While baseline spine dynamics at the apical dendrites of L2/3 pyramidal neurons was similar between adult PSD-95 WT and KO mice, a brief MD (4 d) led to a more than twofold increase (∼126%) in spine elimination in adult PSD-95 KO but not WT mice, and to a ∼70% increase in spine elimination in PSD-95 knockdown neurons in a WT environment. These results in PSD-95-deficient adult V1 neurons are very similar to the ∼100% increase in spine elimination previously observed for L2/3 apical dendrites of juvenile (P28) WT mice after a 3-d MD (19). For L5 apical dendrites of juvenile WT mice, pronounced spine elimination (>70% increase) after a 3-d MD has also been reported (20), but so far not for adult mice beyond the critical period.…”
Section: Discussionsupporting
confidence: 87%
“…One is impressed by the concurrent disappearance and appearance of labeled synaptic elements in 2 days after MD, showing a net drop of them as a result of “bidirectional” changes, in an area examined in vivo under 2‐photon microscopy. Though the reported bidirectional changes are not necessarily derived from the same cells, a clear correlation was found between the extent of synaptic adjustment of a postsynaptic density marker and OD changes assessed by VEP amplitudes (Sun, Espinosa, Hoseini, & Stryker, 2019). The authors made a significant step forward in the integration of physiology and morphology in the ODP quest.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that axonal boutons exhibit plasticity during a novel experience. For example, auditory fear conditioning induces the formation of boutons on axons projecting from the lateral amygdala to L1 dendritic spines of L5 auditory cortical neurons [68], and monocular deprivation induces a small and slow formation rate increase and elimination rate decrease in the axonal boutons of L2/3 neurons in the visual cortex [69]. By contrast, the axonal boutons of L2/3 neurons are stable in the barrel cortex in adult mice in an enriched environment [57].…”
Section: Plos Onementioning
confidence: 99%